Investigation of the kinetics and mechanism of low endotoxin recovery in a matrix for biopharmaceutical drug products. (May 2018) - Reich, Johannes; Tamura, Hiroshi; Nagaoka, Isao; Motschmann, Hubert
Abstract: The inability to detect endotoxin added to undiluted drug samples has been called: Low Endotoxin Recovery (LER). The phenomenon has caused concerns amongst drug manufacturing quality control scientists in that manufactured solutions contaminated with endotoxin could show false-negative results via routine Limulus -based tests. The time-dependent appearance of LER has been analyzed in detail to provide a better understanding of the mechanism. The assumption has been that the root-cause of LER involves the interplay of endotoxin with surfactants and results in aggregate structures that are complexed with surfactants. The endotoxin molecules when complexed with surfactants are not accessible for Limulus- based detection. The results demonstrate a predominant role of complex-forming agents. It was shown that although the presence of surfactants is a strong prerequisite for masking, it does not determine the kinetics of endotoxin masking. Interestingly, the endotoxin concentration itself had no substantial impact on LER kinetics. By adjusting the ratios of complex-forming constituents, including surfactant, chelator and endotoxin, and by testing the order in which the constituents are added, a new model for simulating masking kinetics has been determined. Our work provides for the first time a model to simulate masking kinetics of endotoxin which lends a better understanding of LER.